Process evaluation protocol for the BeST? Services trial. (March 2022) - Kainth, Gary; Turner, Fiona; Crawford, Karen; Watson, Nicholas; Dundas, Ruth; Minnis, Helen
Background: Outcomes for children who have been received into state care due to maltreatment or neglect are very poor in comparison to the general population. A mental health focussed intervention is being trialled in the UK which seeks to improve outcomes for such children. Although the main study is concerned with outcome evaluation (child mental health measures), a robust process evaluation adds nuance to the findings by examining the relationship between the interventions, the participants and the context-thereby determining what works, for whom and in what context. This paper sets out the protocol for that process evaluation. Methods: The process evaluation is embedded within a Randomised Control Trial and uses Realist Evaluation as its theoretical framework. It sets out the mechanisms of change that are used to effect positive outcomes and outlines the various aspects of the context (including service provision and the legal system that provides the statutory basis for involvement with families). Data collection is primarily qualitative and takes place with a large group of stakeholders. The analysis of the interplay between context, mechanisms and outcomes will provide a richer understanding of the main trial outcomes. Discussion: The nature of the interaction between the social, legal and practice context is complex. The use of a variety of methods including case studies, focus groups and analysis of routine data are justified and it is argued that they will provide for greater understanding of the nature of the interactions within such a challenging context.